Tru64 UNIX troubleshooting diagnosing and correcting system problems - Moore, Martin L.; Hancock, Steven M. (Amsterdam ; Boston : Digital Press, 2003)
Dealing with system problemsfrom user login failures to server crashes--is a critical part of a system administrator's job. A down system can cost a business thousands of dollars per minute. But there is little or no information available on how to troubleshoot and correct system problems; in most cases, these skills are learned in an ad-hoc manner, usually in the pressure-cooker environment of a crisis. This is the first book to address this lack of information. The authors (both experienced Tru64 UNIX support engineer for Compaq) systematically present the techniques and tools needed to find and fix system problems. The first part of the book presents the general principles and techniques needed in system troubleshooting. These principles and techniques are useful not only for UNIX system administrators, but for anyone who needs to find and fix system problems. After this foundation, the authors describe troubleshooting tools used in the UNIX environment. The remainder of the book covers specific areas of the Tru64 UNIX operating system in detail: listing common problems, their causes, how to detect them, and how to correct them. Each chapter includes a "Before You Call Support" section that details the most important things to check and correct before it's necessary to call Compaq technical support. The authors also include decision trees to help the reader systematically isolate particular problem types. "Before You Call Tech Support" sections Tables and diagrams for quick access to precise data Decision trees to help choose the best way to troubleshoot a particular problem.
Principles and techniques -- Tools and resources -- User accounts and security -- System failures -- System performance -- Networking -- Storage -- File systems -- System configuration -- System administration -- Display problems.
Includes bibliographical references (p. 319-321) and index.
Keywords: UNIX (Computer file); Operating systems (Computers).; Software maintenance; Debugging in computer science; Electronic books